2013
DOI: 10.5585/conssaude.v12n1.3877
|View full text |Cite
|
Sign up to set email alerts
|

Fisioterapia convencional vs. wiiterapia: efeitos na força muscular de mulheres idosas com osteoartrite de joelho

Abstract: Introdução: A força muscular diminui nos idosos portadores de osteoartrite de joelho. Objetivo: Avaliar os efeitos da fisioterapia convencional (FC) e da wiiterapia na força muscular de idosas com osteoartrite (OA) de joelho e comparar os resultados pré- e pós-intervenção. Métodos: Realizou-se estudo longitudinal, intervencionista, envolvendo 71 idosas (GI=33 (FC) e GII=38 (wiiterapia)), ≥60 anos, que responderam um questionário, sendo realizadas avaliação isocinética nas velocidades de 120, 180 e 240o/s e 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In the knee extensor and flexor concentric isokinetic torque analysis, an increase in peak torque for both groups after the intervention was obtained, regardless of the angular velocities adopted. This finding is consonant with the study by Wibelinger et al 20 that compared the effects of conventional physiotherapy with those of virtual reality in relation to the muscle strength of 71 elderly females with knee osteoarthrosis. The elderly females were divided into two groups, using angular velocities similar to those used in the present study and they observed an increase in the peak torque for both groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the knee extensor and flexor concentric isokinetic torque analysis, an increase in peak torque for both groups after the intervention was obtained, regardless of the angular velocities adopted. This finding is consonant with the study by Wibelinger et al 20 that compared the effects of conventional physiotherapy with those of virtual reality in relation to the muscle strength of 71 elderly females with knee osteoarthrosis. The elderly females were divided into two groups, using angular velocities similar to those used in the present study and they observed an increase in the peak torque for both groups.…”
Section: Discussionsupporting
confidence: 88%
“…8 The knee extensor and flexor muscles of the dominant lower limb were submitted to an isometric and concentric dynamometric isokinetic evaluation. This standardization was adopted based on the literature, 8,19,20 which showed the peak torque between lower limbs and found no significant difference between the dominant and non-dominant limbs. Therefore, for the present study, only the dominant lower limb was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…At present there are various types of treatments for physical rehabilitation, each one of them has its benefits and harms, some authors made comparisons between Conventional Physiotherapy and Wiitherapy (Wibelinger et al, 2013), on the other hand, Vibrotherapy is applied (Rodríguez et al, 2006), and "Electro shock, electromagnetic waves, acupuncture, suction cups, among others" (Colegio profesional de Fisioterapeutas de Andalucía, 2012).…”
Section: Introductionmentioning
confidence: 99%